MENINGKATKAN KEMAMPUAN MENULIS CERITA NARASI MELALUI PENDEKATAN KONTEKSTUAL DENGAN MEDIA GAMBAR BERSERI PADA SISWA KELAS VII SMP NEGERI 9 MODEL KOTASORONG TAHUN PELAJARAN2018/2019 - Soulisa, Irwan (Jurnal Pena Indonesia, 2018)
This research aims to find out how the development especially in terms of writing a narrative through contextual approach with media images in a series that could serve as an alternative in the learning process in schools. The form of this research is the research action class. The subject of the research is grade VII-G junior Country 9 city of Sorong of 37 students, consists of 19 men and 18 women. This research was conducted in two cycles and pengumpuan data on engineering research is engineering tests and nontes. Test techniques in the form of the description that is a fantasy story writing and techniques of nontes i.e. observation and interview. Technique of data analysis in this study includes quantitative data analysis to analyze the results obtained from a test write fantasy, while qualitative data analysis technique used to see the effectiveness of the use of the approach contextual media pictures glow and see changes in student behavior during and after the learning process.           The results of this study showed that the ability to write fantasy stories have elevated from before the implementation cycle or pratindakan. The increase occurred in every aspect, such as aspects of the structure in the pratindakan there are 26 students (70.27%) students has been completed, and at the end of the cycle reached 37 pupils (100%) has been completed. The increase also occurred on the content that was originally 4 students (10.81%), and at the end of the cycle there are 37 pupils (100%) has been completed. As well as an increase in the use of the language on the pratindakan aspects of 5 students (13.51%) to 30 students (81.08%) at the end of the cycle. Therefore, the increase also occurred on the number of students who are finished in a fantasy story writing skills, and ketuntasan in the pratindakan only achieved by 3 students (8.10%) then increased at the end of the cycle be 29 students (78.37%) completely from the 37 students who were given the test. Ketuntasan is measured from the KKM is on the school that is 75. This causes the average value of the class be increased from pratindakan phase obtained average value of 42.24 and increased to 77.70 at the end of the cycle.